A Canopy Flow Equation for Erosion Control Geosynthetics. Issue 3 (1st January 2001) - Hytiris, N.; Addison, P.S.; McKay, D.J.
Abstract : A novel experimental test programme for erosion control geosynthetic mattings, i.e., geomats, is described. Using a laser Doppler anemometer, the velocities have been examined within the flow field at the fluid-geomat interface. Initial analysis of the test results has lead to a modified log-law equation for the downstream flow velocities above the geomat. This equation has the same form as canopy flow equations used in meteorology to describe the velocity profiles above vegetative canopies in the atmospheric boundary layer. The canopy flow equation for erosion control geotextiles is discussed herein.